(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A study on comparative productive efficiency and feasibility of lentil varieties both at relay and minimum tillage were conducted at the Regional Agricultural Research Station, BARI, Ishurdi, Pabna, Bangladesh during the Rabi season of 2007-08 and 2008-09. Three lentil varieties viz. BARI Masur-2, BARI Masur-3 and BARI Masur-4 and two sowing methods viz. relay sowing and furrow sowing (Minimum tillage) were compared. The highest seed yield (1.59 t/ha) was obtained from BARI Masur-4 because of highest number of pods/plant and plant population/m2 while lowest from BARI Masur-2 (1.39 t/ha). The sowing methods had significant effect on the seed yield of lentil. Crops sown in furrows produced higher seed yield (1.60 t/ha) than that of crops in relay sowing. The interaction effect between varieties and sowing methods also had significant effect on the seed yield and yield attributes. The lentil variety BARI Masur-4 when grown in furrows gave the highest seed yield (1.70 t/ha). Though seed yield and gross return were highest in furrow sowing but highest benefit cost ratio (4.67) was found in relay sowing method. Bangladesh J. Agril. Res. 40(2): 271-278 June 2015